Digital Marketing Optimization: Empowering Market Growth for MSMEs in Kahuku Village, East Likupang - Prabantoro, Gatot; Mais, Rimi Gusliana; Megayani, Megayani; Mustika, Maya; Ardheta, Preztika Ayu; Faruqi, Faris; Anthonio, Dean Salomo; Kawung, Goerge M.V.; Siwu, Hanly F.J (Santoso Academy Network, 2024)
Community Service is a core element of the Tridharma of Higher Education and a key responsibility of lecturers. This PKM (Community Service Program) focuses on Micro, Small, and Medium Enterprises (MSMEs) in Kahuku Village, Likupang Timur District, North Minahasa Regency, North Sulawesi Province. The goal is to optimize digital marketing to expand the market reach of MSMEs by using and managing information on the Google My Business platform. The PKM activities are conducted in a hybrid format, combining online sessions via Zoom and offline sessions in Kahuku Village on October 6, 2023, from 08:00 to 12:00 WIB. The implementation team includes lecturers from STIE Indonesia Jakarta, in collaboration with the Faculty of Economics and Business at Sam Ratulangi University, Nusa Utara Tahuna State Polytechnic, New Jerusalem Theological College Manado, and Pioneer Manado STIE. The primary participants are MSME operators in Kahuku Village. After participating in the program, participants are expected to enhance their business presence by showcasing their products on Google My Business. This initiative aims to help MSMEs in Kahuku Village attract tourists through effective digital marketing strategies, increase product visibility, and positively impact local economic development.